An innovative leg self-exercise to reduce knee pain severity among the elderly people in Thailand - Tanthanapanyakorn, Phannathat; Khantikulanon, Nonlapan; Weschasat, Tassanapan (International Journal of Public Health Science (IJPHS), 2024)
Osteoarthritis (OA) is a prevalent health issue that has consistently risen in occurrence among the elderly in Thailand. This issue holds significant importance within Thailand's healthcare system. This research was allocated to the quasi-experimental study aimed at assessing the effectiveness of leg self-exercises for reducing knee pain severity among the elderly. The total sample size was 108 elderly people recruited into the study with an Oxford Knee Score (OKS) between 20 and 48. The participants were divided into two groups: the intervention group received leg self-exercise with a plank for six weeks, and the control group: received health education booklets. All parameters were compared between and within each group using the independent t-test and paired sample t-test in data analysis. At the three-month follow-up, the results revealed that the OKS and self-exercise behavior in the intervention group had considerably increased more than those in the control group (p<0.001). Compared with the baseline and three-month follow-up, the within comparison, the OKS, and self-exercise behavior were significantly improved (p<0.001). The leg self-exercise with the plank program can lessen the degree of knee discomfort in the elderly and be used to impose and produce recommendations for supporting healthy policies.